SISTEM MANAJEMEN RISIKO KONTAMINASI PADA RANTAI PASOK PANGAN (STUDI KASUS : SUSU PASTEURISASI) - Nindya Malvins Trimadya, Hartrisari Hardjomidjojo, dan Elisa Anggraeni (Jurnal Teknologi Industri Pertanian, 2018)
Intentional contamination threats to food supply chain has increased. Risk management can be used to handle such threats. Risk management methods such as International Organization for Standardization (ISO) 22000, Hazard Analysis and Critical Control Points (HACCP) can only be applied for unintentional contamination threats. The objectives of this research was to develop a model of risk management for intentional contamination threat on pasteurized milk supply chain in Indonesia. A case study using Threat Assessment Critical Control Point (TACCP) was conducted in PT XYZ to apply the model. The results showed that the threats can be divided into food fraud risk and food defense risk.  The threat to this pasteurized product from this company could be classified as low risk by applying actions, such as prevention, detection, and deterrence.Keywords : food defense, food fraud, intentional contamination, pasteurized milk